A method for preparing high-purity fluoride salts
Patent Information
- Application Number
- CN202611434632.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
湿法工艺中,一般使用水溶性锂盐和氢氟酸(或氟盐)沉淀结晶,但是该过程难以控制,晶粒生长不均一,由于快速结晶导致大颗粒往往包裹母液中的杂质和水分,严重降低产品纯度
[0005]本发明旨在至少解决相关技术中存在的技术问题之一。为此,本发明的目的在于提供一种高纯氟盐的制备方法。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluoride salt preparation technology, and in particular to a method for preparing high-purity fluoride salts. Background Technology
[0002] Lithium fluoride (LiF) is an important class of inorganic fluorides, widely used in lithium-ion battery electrolytes, optical glass, ceramics, and the nuclear industry. In lithium-ion battery systems, lithium fluoride serves as an electrolyte additive and is also a crucial raw material for preparing lithium hexafluorophosphate; its purity directly impacts the overall battery performance. In applications such as chemical reactions and crystal sintering, small-diameter lithium fluoride particles have a large specific surface area and high reactivity, which can improve the efficiency and uniformity of electrolyte preparation, optimizing battery energy density and cycle life. Furthermore, nanoscale small-diameter lithium fluoride particles melt more readily and uniformly at high temperatures, forming a melt with uniform density, effectively improving the quality of optical single crystal preparation. Therefore, developing methods for preparing small-diameter, high-purity (≥5N) lithium fluoride is of great significance.
[0003] Currently, there are two main types of lithium fluoride preparation processes: wet and dry processes. In wet processes, water-soluble lithium salts and hydrofluoric acid (or fluoride salts) are typically used for precipitation and crystallization. However, this process is difficult to control, resulting in uneven grain growth. Rapid crystallization often leads to large particles encapsulating impurities and moisture from the mother liquor, severely reducing product purity. Introducing conventional organic components (ethanol, PEG, etc.) makes it difficult to control particle size and effectively improve product purity. Dry processes (such as zone melting) generally suffer from high energy consumption and low raw material utilization, and are difficult to produce small-particle-size lithium fluoride with uniform particle size. Using ball milling to refine the finished product particle size is not only time-consuming but also results in low single-batch production capacity.
[0004] Therefore, how to provide a method for preparing fluoride salts with small particle size and high purity is a technical problem that urgently needs to be solved. Summary of the Invention
[0005] The present invention aims to at least solve one of the technical problems existing in the related art. Therefore, the object of the present invention is to provide a method for preparing high-purity fluoride salts.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a high-purity fluoride salt, comprising: Add betaine derivative to a soluble lithium salt aqueous solution and stir to allow the betaine derivative to reach coordination equilibrium with lithium ions to obtain a liquid containing a lithium-betaine derivative complex. The structural formula of the betaine derivative is shown below: ; The molar ratio of the betaine derivative to the soluble lithium salt is (0.1–0.2):1; A soluble fluoride salt aqueous solution was added dropwise to the liquid containing the lithium-betaine derivative complex. After the addition was complete, the solution was filtered and treated at high temperature to obtain a high-purity fluoride salt. The molar ratio of soluble fluoride salt to soluble lithium salt is (0.9–1.1):1; The high-temperature treatment was carried out in an inert gas atmosphere at a temperature of 340–360°C for 3–5 hours. The high-purity fluoride salt is lithium fluoride, and the purity of the high-purity fluoride salt is ≥99.999%.
[0007] Betaine derivatives mainly exert their effects through the following reaction mechanisms: The carboxylate terminus of betaine derivatives can react with Li in solution. + Reversible coordination occurs, forming a kinetically stable lithium-betaine derivative complex. This process reduces the effective concentration of free lithium ions and slows down the Li-betaine reaction. + With F - The increased binding rate transforms the traditional rapid precipitation process into a more uniform nucleation process, thus avoiding impurity encapsulation caused by localized ion supersaturation. Furthermore, the LiF crystal nuclei formed in the initial stage of the reaction possess positively charged Li atoms on their surface. + The active site can be anchored by the anionic group of the betaine derivative; at the same time, the positively charged quaternary ammonium group at the other end of the molecule extends outward to build a protective layer with a positive charge and large steric hindrance around the crystal nucleus, thereby inhibiting the further growth of lithium fluoride crystals.
[0008] Preferably, the synthesis of the betaine derivative includes: Using N,N-dimethyl-2-phenylethylamine and sodium 3-chloropropionate as raw materials, and water containing inorganic base as reaction solvent, the crude betaine derivative was obtained by reflux at 70-90°C for 5-12 hours. The crude betaine derivative was washed with an organic solvent and then evaporated by rotary evaporation to obtain the betaine derivative.
[0009] Preferably, the molar ratio of N,N-dimethyl-2-phenylethylamine to sodium 3-chloropropionate is (0.9–1.1):1; The inorganic base is sodium hydroxide; The organic solvent is dichloromethane or ethyl acetate.
[0010] Preferably, the mass ratio of sodium hydroxide to water is (2-5):20000.
[0011] Preferably, the soluble lithium salt is lithium nitrate.
[0012] Preferably, the stirring speed is 600-800 rpm and the stirring time is 1-3 hours.
[0013] Preferably, the soluble fluoride aqueous solution is added dropwise to the liquid containing the lithium-betaine derivative complex at a rate of 0.1 to 1 mL / min.
[0014] Preferably, the particle size of the high-purity fluoride salt is 100-110 nm.
[0015] Preferably, the soluble fluoride salt is ammonium fluoride.
[0016] Preferably, the inert gas is nitrogen.
[0017] The above-described one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects: This invention provides a method for preparing high-purity fluoride salts, comprising: adding a betaine derivative to a soluble lithium salt aqueous solution, stirring until homogeneous, to obtain a liquid containing a lithium-betaine derivative complex; the derivative acts as a complexing / chelating agent, coordinating with lithium ions in the aqueous solution to generate a lithium-betaine derivative complex. Specifically, the betaine derivative can, on the one hand, pre-enrich and directionally complex lithium ions, reducing the tendency for co-precipitation of lithium with metal impurities such as calcium, magnesium, iron, sodium, and potassium, and inhibiting subsequent co-precipitation of impurities; on the other hand, it regulates the form of lithium species, creating conditions for subsequent reaction with fluoride ions to generate a precursor precipitate with uniform particle size and few impurities; an appropriate addition ratio ensures sufficient complexation of lithium ions while avoiding excessive residual organic ligands, reducing the burden on subsequent high-temperature removal of organic impurities.
[0018] A soluble fluoride aqueous solution was added dropwise to a liquid containing a lithium-betaine derivative complex; the molar ratio of soluble fluoride to soluble lithium salt was controlled at (0.9–1.1):1; high-temperature treatment was carried out under an inert gas atmosphere at a temperature of 340–360 °C for 3–5 h; after the fluoride ions were slowly added to the system, they reacted with the lithium ions in the complex to form a lithium fluoride precursor precipitate. This dropwise addition method facilitates slow nucleation and crystal growth, reducing the problems of impurity encapsulation and adsorption caused by rapid precipitation bursts; the near 1:1 molar ratio ensures sufficient reaction between the lithium and fluoride sources, reducing lithium residue loss or the introduction of new impurities due to excessive fluoride, laying the foundation for the preparation of high-purity lithium fluoride. High-temperature treatment in an inert gas atmosphere can decompose and remove betaine organic complexing agents entrained and adsorbed in the precursor precipitate, completely removing organic components and avoiding organic carbon impurities remaining in the lithium fluoride product. The inert atmosphere (nitrogen, argon, etc.) isolates the lithium fluoride from air, preventing it from being oxidized or hydrolyzed by water vapor at high temperatures to generate byproducts such as lithium hydroxide and lithium oxide. High-temperature heat treatment achieves the effects of sintering purification and crystal perfection, further removing residual trace volatile impurities, resulting in lithium fluoride with small particle size and high purity.
[0019] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0020] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the betaine derivative provided in Example 1 of the present invention ( 1 H NMR).
[0021] Figure 2 This is a scanning electron microscope (SEM) image of the high-purity lithium fluoride powder provided in Example 2 of the present invention.
[0022] Figure 3 This is a particle size distribution curve of high-purity lithium fluoride powder provided in Embodiment 2 of the present invention.
[0023] Figure 4 This is an infrared test result image of lithium fluoride powder before and after the high-temperature treatment process provided in Embodiment 2 of the present invention.
[0024] Figure 5 This is a SEM image of lithium fluoride crystals provided in Comparative Example 1 of this invention.
[0025] Figure 6 This is a particle size distribution curve of lithium fluoride powder provided in Comparative Example 4 of the present invention. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The following embodiments are used to illustrate this invention, but cannot be used to limit the scope of this invention.
[0027] In the following embodiments, unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used are commercially available, unless otherwise specified, and are carried out in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions.
[0028] Example 1 Preparation of betaine derivatives The synthesis route is shown below: ; The specific synthesis process is as follows: N,N-dimethyl-2-phenylethylamine (0.1 mol) and sodium 3-chloropropionate (0.1 mol) were added to a reaction vessel containing 200 mL of deionized water, which pre-dissolved 50 mg of NaOH. Stirring was started, and the reaction system was heated to 80 °C under continuous stirring. The mixture was then refluxed for 8 hours. After the reaction was complete, the system was allowed to cool naturally to room temperature to obtain a crude reaction solution. 200 mL of dichloromethane was added to this crude reaction solution for extraction. After thorough shaking and separation, the organic phase was discarded, and the aqueous phase was retained. The aqueous phase was concentrated under reduced pressure to remove most of the water, and then vacuum dried to obtain a white solid powder, which was the target betaine derivative. 1 H NMR spectra, such as Figure 1 As shown, a set of multiplets appears in the aromatic region at δ = 7.19–7.31 ppm, with an integrated hydrogen number of approximately 5H, corresponding to hydrogen atoms on the monosubstituted benzene ring; the signals at δ = 3.23–3.28 ppm, δ = 3.11 ppm, and δ = 2.77–2.80 ppm are attributed to the methylene (-CH2-) hydrogen atoms bonded to nitrogen atoms on the molecular chain; the singlet at δ = 2.88 ppm has an integrated value of approximately 6H, representing two equivalent methyl-N groups on a quaternary ammonium group. + The characteristic hydrogen signal of (CH3)2. The baselines of each signal peak are stable and the peak shapes are clear. The hydrogen integral ratio is basically consistent with the theoretical number of hydrogen atoms in the target molecule. There is no obvious interference from impurity peaks. The above results indicate that the obtained product has high purity and a betaine-type amphoteric surfactant containing a benzene ring structure has been successfully synthesized.
[0029] Example 2 The process for preparing high-purity lithium fluoride is as follows: Prepare 500 mL of a 1 mol / L lithium nitrate aqueous solution in a polytetrafluoroethylene beaker. Add 0.1 mol of a betaine derivative to this solution, start mechanical stirring at 700 rpm, and continue stirring for 2 hours to allow the betaine derivative to fully coordinate and complex with lithium ions, obtaining a liquid containing a lithium-betaine derivative complex. Maintain the temperature of this liquid system at approximately 25°C, and while continuously stirring at 700 rpm, slowly add 250 mL of a 2 mol / L ammonium fluoride aqueous solution at a dropping rate of approximately 0.5 mL / min. This dropping rate ensures a slow and uniform reaction between fluoride ions and the complexed lithium ions, avoiding excessively high local concentrations that could lead to particle agglomeration and impurity encapsulation, thus ensuring uniform growth of the precursor particles. After all the ammonium fluoride aqueous solution was added dropwise, the reaction was continued at a constant temperature with stirring for about 45 minutes. Then, the reaction system was filtered through a 0.22 μm filter membrane to separate the solid precursor product. The solid filter cake was washed three times with 500 mL of deionized water to remove soluble ammonium nitrate, excess raw material, and residual mother liquor adsorbed on the product surface. The washed filter cake was transferred to a tube furnace and treated at 350 °C for 4 hours under a nitrogen atmosphere (flow rate of 0.5 L / min) to obtain high-purity lithium fluoride powder.
[0030] SEM images of high-purity lithium fluoride powder, as shown below. Figure 2 As shown in the figure, the diameter of the lithium fluoride powder particles is concentrated at around 100 nm, and the appearance is neat and uniform, indicating that ultrafine lithium fluoride nanoparticles have been successfully prepared.
[0031] 5 mg of the high-purity lithium fluoride sample prepared above was dispersed in 5 mL of ultrapure water and mechanically shaken for 5 min to suspend the particles in the solution. The particle size distribution of the high-purity lithium fluoride powder sample was tested using a dynamic light scattering instrument, and the results are shown in Table 1.
[0032] Table 1. Particle size test results of high-purity lithium fluoride
[0033] Particle size distribution curve of high-purity lithium fluoride powder, as shown in the figure. Figure 3 As shown in the figure, the volume density curve exhibits a single, sharp, normally distributed peak, without any extraneous peaks or obvious tailing. The main peak particle size is approximately 101 nm. The volume accumulation curve has a narrow rising range. Combined with the data provided in Table 1, it can be seen that the high-purity lithium fluoride powder prepared in this embodiment has a concentrated particle size (mainly concentrated in the range of 100–110 nm), a regular morphology, a small particle size distribution width, and uniform particle size.
[0034] To demonstrate that the lithium fluoride nanoparticles prepared in this embodiment reach the 5N (purity ≥99.999%) level, inductively coupled plasma (ICP) was used to perform full elemental scanning and quantitative analysis of metal impurities in the high-purity lithium fluoride powder. The process is as follows: 200 mg of the sample to be tested was weighed and placed in a polytetrafluoroethylene digestion cup that had been acid-washed and purified. 2 mL of concentrated nitric acid (concentration approximately 68%) and 0.5 mL of ultrapure water were added. The mixture was gently digested on a 120°C heating plate until completely dissolved. Then, 100 μL of boric acid aqueous solution (5% wt) was added, and the mixture was stirred evenly before being transferred to a clean volumetric flask. The volume was adjusted to 50 mL with ultrapure water. At the same time, a blank control solution was prepared. The detection results are shown in Table 2.
[0035] Table 2 Purity test results of high-purity lithium fluoride
[0036] The purity of high-purity lithium fluoride nanoparticles is not less than 99.99987% when the LiF content is 100% minus the sum of the measured values of metal impurity elements.
[0037] To ensure effective removal of residual betaine derivatives after high-temperature treatment, infrared spectroscopy was performed on lithium fluoride powder before and after the high-temperature treatment process. The results are as follows: Figure 4 As shown in the figure, it can be seen that the sample before calcination was at 3000 cm⁻¹ -1 1500cm -1 1400cm -1 1200cm -1 Characteristic absorption peaks of aromatic ring CH, benzene ring skeleton C=C, carboxylate CO, and quaternary ammonium CN bonds appeared near the wavenumber, proving the presence of betaine organic activator on the surface of lithium fluoride precursor; after calcination at 350℃ under nitrogen atmosphere, the absorption peaks of the organic functional groups corresponding to the betaine derivative disappeared, indicating that the betaine derivative was successfully removed, and lithium fluoride product with almost no organic residue was obtained.
[0038] Comparative Example 1 Except for the absence of betaine derivatives, the preparation steps were identical to those in Example 2 for the preparation of high-purity lithium fluoride powder. The SEM image of the obtained lithium fluoride powder is shown below. Figure 5 As shown in the figure, the lithium fluoride particles prepared without the addition of betaine derivatives are mainly in the micrometer range, with a wide particle size distribution. Some crystals agglomerate and adhere, resulting in poor particle uniformity. This result demonstrates that betaine derivatives can regulate and reduce the particle size of lithium fluoride and improve particle dispersibility.
[0039] Comparative Example 2 Except for replacing the betaine derivative with hexadecyltrimethylammonium bromide (CTAB), the remaining preparation steps were consistent with the preparation process of high-purity lithium fluoride powder in Example 2. A small amount of millimeter-sized lithium fluoride fragments were ultimately generated, indicating that a significant amount of reactants in the reaction system did not participate in the reaction. These results demonstrate that although the positively charged quaternary ammonium head groups can adsorb onto the negatively charged F- group on the surface of the lithium fluoride crystal nucleus... - However, the CTAB molecule lacks anionic groups such as carboxylate groups that can coordinate with Li+, making it unable to effectively complex free lithium ions. This hinders the reduction of the effective concentration of Li+ in the solution and slows down the nucleation rate, allowing the reaction to proceed at a relatively fast rate. After nucleation, CTAB can only provide limited steric hindrance through electrostatic adsorption. This single positive charge adsorption cannot fundamentally inhibit the continuous growth of the nuclei, ultimately resulting in disordered and rapid growth of lithium fluoride crystals. Simultaneously, fluoride ions have a strong binding affinity to CTAB, and a large amount of reactants combine with organic cations, thus failing to participate in the lithium fluoride crystallization reaction.
[0040] Comparative Example 3 Except for replacing the betaine derivative with sodium dodecyl sulfate (SDS), the remaining preparation steps were consistent with the preparation process of high-purity lithium fluoride powder in Example 2, ultimately producing millimeter-sized lithium fluoride fragments. This is mainly because SDS molecules lack the ability to react with Li... + The specific functional groups undergoing reversible coordination exhibit weak complexation of terminal sulfate groups with free lithium ions, thus failing to effectively regulate the nucleation rate. Simultaneously, the dodecyl hydrophobic chain of SDS readily forms micelles in solution, which can enrich Li⁻. + and F - The formation of localized supersaturated regions exacerbates rapid crystallization and leads to impurity encapsulation.
[0041] Comparative Example 4 In addition to replacing the betaine derivative with commercially available dodecyl betaine (BS-12). Except for the preparation steps, all other preparation steps were consistent with the preparation process of high-purity lithium fluoride powder in Example 2, ultimately producing granular lithium fluoride crystals. The finer powder was sieved and sent to dynamic light scattering test to determine its particle size distribution (the detection method was the same as in Example 2). The results are shown in Table 3 and... Figure 6 As shown.
[0042] Table 3
[0043] From the data provided in Table 3 and Figure 6It can be seen that the lithium fluoride particles prepared using BS-12 have poor regularity, with micron-sized particles, wide distribution range, and poor uniformity. BS-12, like betaine derivatives, belongs to the betaine-type amphoteric surfactants, with molecules carrying both quaternary ammonium positive charges and carboxylate negative charges. However, BS-12 has a straight-chain dodecyl hydrophobic chain, lacking rigid groups such as benzene rings, resulting in a highly flexible molecular chain and varied spatial conformations. This flexible structure leads to insufficient density and stability of the adsorption layer constructed by BS-12 on the LiF crystal nucleus surface, limiting the steric hindrance effect it can provide. Simultaneously, the hydrophobic effect generated by the straight-chain alkyl group easily promotes the spontaneous formation of micelles by BS-12 molecules in solution, reducing the concentration of free active agents that effectively regulate the crystal nucleus in the system, ultimately weakening its effect on LiF. + The coordination regulation effect is limited. Therefore, although BS-12 has a certain particle size regulation capability, it cannot obtain nanoscale products with uniform particle size.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-purity fluoride salt, characterized in that, include: Add betaine derivative to a soluble lithium salt aqueous solution and stir to allow the betaine derivative to reach coordination equilibrium with lithium ions to obtain a liquid containing a lithium-betaine derivative complex. The structural formula of the betaine derivative is shown below: ; The molar ratio of the betaine derivative to the soluble lithium salt is (0.1–0.2):1; A soluble fluoride salt aqueous solution was added dropwise to the liquid containing the lithium-betaine derivative complex. After the addition was complete, the solution was filtered and treated at high temperature to obtain a high-purity fluoride salt. The molar ratio of soluble fluoride salt to soluble lithium salt is (0.9–1.1):1; The high-temperature treatment was carried out in an inert gas atmosphere at a temperature of 340–360°C for 3–5 hours. The high-purity fluoride salt is lithium fluoride, and the purity of the high-purity fluoride salt is ≥99.999%.
2. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The synthesis of the betaine derivative includes: Using N,N-dimethyl-2-phenylethylamine and sodium 3-chloropropionate as raw materials, and water containing inorganic base as reaction solvent, the crude betaine derivative was obtained by reflux at 70-90°C for 5-12 hours. The crude betaine derivative was washed with an organic solvent and then evaporated by rotary evaporation to obtain the betaine derivative.
3. The method for preparing high-purity fluoride salts as described in claim 2, characterized in that, The molar ratio of N,N-dimethyl-2-phenylethylamine to sodium 3-chloropropionate is (0.9–1.1):1; The inorganic base is sodium hydroxide; The organic solvent is dichloromethane or ethyl acetate.
4. The method for preparing high-purity fluoride salts as described in claim 3, characterized in that, The mass ratio of sodium hydroxide to water is (2-5):20000.
5. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The soluble lithium salt is lithium nitrate.
6. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The stirring speed is 600-800 rpm, and the stirring time is 1-3 hours.
7. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The soluble fluoride aqueous solution is added dropwise to the liquid containing the lithium-betaine derivative complex at a rate of 0.1–1 mL / min.
8. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The particle size of the high-purity fluoride salt is 100-110 nm.
9. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The soluble fluoride salt is ammonium fluoride.
10. The method for preparing high-purity fluoride salts as described in claim 1, characterized in that, The inert gas is nitrogen.